Treatment of Irritable Bowel Syndrome with Saccharomyces Cerevisiae - Al-helo, Amjad Atef Suliman (Journal of medical and pharmaceutical sciences, 2019)
Aim: To evaluate the effect of probiotic Saccharomyces Cerevisiae in the treatment of Irritable Bowel Syndrome in a randomized, double-blind placebo-controlled clinical trial. Methods: A randomized, double-blind placebo-controlled clinical trial has been performed in 347 adults, diagnosed with IBS (Rome III criteria). Subjects were randomized to receive 1000 mg BID of Saccharomyces Cerevisiae daily for four-week, product 177, placebo 170. IBS symptoms (abdominal pain/discomfort, bloating/distension, bowel movement difﬁculty) and changes in stool frequency and consistency were recorded daily by the patients and assessed weekly by the investigator. Result: Improvement of Gastrointestinal symptoms was significantly higher in the product group, compared to the placebo, on (abdominal pain/discomfort, bloating/distension, bowel movement difﬁculty, with stool modification), p-value < 0.001 in the treated group, and the ratio between groups (130 vs. 47), (73.4% vs. 27.64%). Conclusion: Saccharomyces Cerevisiae significantly improves irritable bowel syndrome symptoms and is well tolerated